1998
DOI: 10.1007/bf03038479
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the micronucleus assay as a biological dosimeter using cytokinesis-blocked lymphocytes from cancer patients receiving fractionated partial body-radiotherapy

Abstract: The micronucleus assay appears to offer a reliable and consistent method for equivalent whole body radiation dose estimation, although our findings should be confirmed using lymphocytes from radiotherapy patients with tumors at anatomical sites other than the pelvis. Except at doses lower than about ).4 Gy, the method yields dose estimates acceptably close to "true" physically determined doses. The assay can be performed relatively rapidly and can be used as a "first line" biological dosimeter in situations wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…cervical cancer, prostate cancer or Hodgkin's disease. The doses estimated by MN analysis agree quite well with averaged whole body doses calculated from the radiation treatment plans (8,(42)(43)(44)(45). Studies performed in thyroid cancer patients undergoing radioiodine treatment further demonstrated that the CBMN assay is sensitive enough to detect low average whole-body doses from internal exposure scenarios (16,23,46).…”
Section: Applications Of the Cbmn Assay For Biological Dosimetrysupporting
confidence: 58%
“…cervical cancer, prostate cancer or Hodgkin's disease. The doses estimated by MN analysis agree quite well with averaged whole body doses calculated from the radiation treatment plans (8,(42)(43)(44)(45). Studies performed in thyroid cancer patients undergoing radioiodine treatment further demonstrated that the CBMN assay is sensitive enough to detect low average whole-body doses from internal exposure scenarios (16,23,46).…”
Section: Applications Of the Cbmn Assay For Biological Dosimetrysupporting
confidence: 58%
“…There have been many studies showing the utility of the technique in biological dosimetry [3,10,12,16,17,25]. Studies that were performed with radiotherapy patients have also confirmed that MN technique is reliable and conveinent technique in estimating equivalent whole body dose that patient receives during fractional treatment [9,11,26,27,28].…”
Section: Discussionmentioning
confidence: 94%
“…Micronucleus may represent acentric chromosome fragment or a whole chromosome that may be lost during segregation [10]. Micronuclei formation in human peripheral lymphocytes has been shown by the investigators to be a good representative of radiation damage [10,11,12,13]. In this study, MN technique was applied to peripheral blood lymphocytes of the radiotherapy patients having pelvic site tumors in order to verify the correct delivery of the prescribed tumor dose and treatment set-up during their fractionated treatment.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, both of these institutions made significant international research contributions to the radiobiology of photons (X-rays and gamma rays) and published notable studies in areas such as dose-modifying drugs, 26,27 repair, 28,29 the oxygen effect, 30,31,32,33,34,35 metabolic modulation, 36 damage response 37,38,39 and biological dosimetry. 40 Regrettably, after 2000, the cutting of posts and poor prospects for graduates resulted in a sharp decline in radiobiology studies. The three once-thriving laboratories at Groote Schuur Hospital, Tygerberg Hospital and iThemba LABS continue with a much reduced capacity of only five remaining staff members.…”
Section: The Importance Of Developing Scientific Competence In Radiob...mentioning
confidence: 99%